2005
DOI: 10.1097/01.rhu.0000195105.20029.07
|View full text |Cite
|
Sign up to set email alerts
|

Angioimmunoblastic T-Cell Lymphoma-Associated Arthritis

Abstract: Angioimmunoblastic T-cell lymphoma (AITL) is a rare type of non-Hodgkin lymphoma with systemic manifestations, including fever, lymphadenopathy, rash, and rarely arthritis. We report the case of a patient who presented with symmetric inflammatory polyarthritis and skin nodules resembling rheumatoid arthritis (RA). The patient responded initially to low-dose prednisolone, but 12 months later, he developed typical features of AITL. The characteristics of AITL-associated arthritis from 16 additional cases from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Nodular lesions, plaques, purpura and urticarial lesions can also be seen (Martel et al , 2000). Other clinical signs and symptoms (arthralgias or arthritis, pleural effusions, ascitis and/or oedema, lung involvement, neurological manifestations, gastrointestinal involvement) are less common, with a wide variation in their reported frequency (Table I) (Bradley et al , 1981; Kaneki et al , 1999; Tsochatzis et al , 2005; Kang et al , 2007; Lachenal, 2007; Mourad et al , 2008). Overall, most patients have concomitant extranodal disease, and the disease is stage III or IV in more than 80% of cases.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Nodular lesions, plaques, purpura and urticarial lesions can also be seen (Martel et al , 2000). Other clinical signs and symptoms (arthralgias or arthritis, pleural effusions, ascitis and/or oedema, lung involvement, neurological manifestations, gastrointestinal involvement) are less common, with a wide variation in their reported frequency (Table I) (Bradley et al , 1981; Kaneki et al , 1999; Tsochatzis et al , 2005; Kang et al , 2007; Lachenal, 2007; Mourad et al , 2008). Overall, most patients have concomitant extranodal disease, and the disease is stage III or IV in more than 80% of cases.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Data regarding synovial fluid findings in paraneoplastic arthritis are limited. Previous studies reported a synovial fluid cell count ranging between 3,500 and 55,000/mm3 in patients diagnosed with lymphoma [8-9]. …”
Section: Discussionmentioning
confidence: 99%
“…In the literature, uncommon skin lesions of AITL are mostly described in case reports or review articles (Table 2). It is not rare that the patient has a generalized pleomorphic rash composed of several types of rashes, such as macula, papules, maculopapules, [30] 77/M Macules; petechiae; purpura 1 year before Alive (4 month) Seehafer [10] 74/M Petechiae Concurrent Died (3 month) Seehafer [10] 61/M Erythroderma and purpura Concurrent Alive (48 month) Seehafer [10] 57/M Petechiae 10 month before Alive (48 month) Schmuth [31] 73/F Macules; petechiae; purpura 4 week before Alive (4 month) Martel [15] Necrotic purpura, maculopapules and urticaria Died (26 day) Martel [15] Pruritic papulovesicular (prurigo-like) lesion Alive (96 month) Hashefi [32] Maculopapules, petechiae 3 month before Died (23 month) Suarez-Vilela [33] 67/F Sarcoidosis 1 month before Huang [34] 62//M Erythroderma; plaques; nodules 3 year after Died (3 year) Jones [35] 67/M Erythroderma, toxic epidermal necrolysis Concurrent Died (5 month) Tsochatzis [36] 50/M Polyarthritis, subcutaneous nodules Concurrent Died (2 month) Jayaraman [11] 61/M Macules, papules, plaques, and nodules Concurrent Alive (5 year) Ortonne [37] 63/F Nodules, gingival ulceration Ortonne [37] 54/M Maculopapules, hemorragic/necrotic nodules Nassar [5] M nodules, erythroderma, urticaria, petechiae, purpura and so on. Necrotic purpura, polyarthritis, gingival ulceration, erythematous plaques (sometimes annular), toxic epidermal necrolysis, and hemorragic/necrotic nodules are also reported.…”
Section: Discussionmentioning
confidence: 99%